Tau underlies synaptic and cognitive deficits for type 1, but not type 2 diabetes mouse models. - Trujillo-Estrada, Laura Isabel; Nguyen, Cassidy; Da Cunha, Celia; Cai, Lena; Forner, Stefania; Martini, Alessandra C.; Ager, Rahasson; Prieto, Gilberto Aleph; Cotman, Carl; Baglietto-Vargas, David; LaFerla, Frank; Baglietto-Vargas, David (Wiley, 2019)
Diabetes mellitus (DM) is one of the most devastating diseases that currently affects the aging population. Recent evidence indicates that DM is a risk factor for many brain disorders, due to its direct effects on cognition. New findings have shown that the microtubule‐associated protein tau is pathologically processed in DM; however, it remains unknown whether pathological tau modifications play a central role in the cognitive deficits associated with DM. To address this question, we used a gain‐of‐ function and loss‐of‐function approach to modulate tau levels in type 1 diabetes (T1DM) and type 2 diabetes (T2DM) mouse models. Our study demonstrates that tau differentially contributes to cognitive and synaptic deficits induced by DM. On one hand, overexpressing wild‐type human tau further exacerbates cognitive and synaptic impairments induced by T1DM, as human tau mice treated under T1DM conditions show robust deficits in learning and memory processes. On the other hand, neither a reduction nor increase in tau levels affects cognition in T2DM mice. Together, these results shine new light onto the different molecular mechanisms that underlie the cognitive and synaptic impairments associated with T1DM and T2DM.
Keywords: Alzheimer, Enfermedad de - Aspectos moleculares; Diabetes - Modelos animales; Alzheimer's disease; Cognition; Dendritic spines; Diabetes mellitus; Synaptid deficit; Tau